Collaborative Teaching in Magnetic Field Lesson for Students with Deaf and Hard of Hearing (DHH) - Widodo, Agus Pratomo Andi; Nandiyanto, Asep Bayu Dani; Hufad, Achmad (International Journal of Psychosocial Rehabilitation, 2020)
The aims of this study to find out how to teach the magnetic field lesson to students with deaf and hard of hearing (DHH). The study used a single-subject research approach with A-B design (baseline and intervention) in senior high school Banjarmasin. The subject of this study consisted of three students with DHH. The results of the study revealed that the magnetic field lesson can be mastered by students with DHH. This success is due to the division of tasks or collaboration between special teachers and regular teachers. When the regular teacher explains with media, a special teacher plays a role in translating to Sign Language. Not all instructions are translated but only instructions that difficult to understand because basically students with DHH can understand from writing and read the regular teacher’s lips movement. Another factor that shapes an understanding of students with DHH is the student’s seating position. Inappropriate positions, students with DHH can see regular teacher’s face clearly and help them to read regular teacher’s lips movement. Essentially, students with DHH use their visual abilities to learn.